Sosialisasi Kesadaran Pentingnya Self-Esteem Pada Remaja - Niki Anartia; Riska Amaretha; Detya Wiryany; Ridma Meltareza (Jurnal Bhakti Karya dan Inovatif, 2023)
Self-esteem is an important aspect of adolescent self-development. In unfavorable conditions, adolescents who have low self-esteem tend to easily feel inferior, insecure, and prone to psychological problems. This service aims to increase awareness of the importance of self-esteem in adolescents in Arjasari Village through community service programs. The method used is a participatory approach involving youth as active participants in program development. This program includes group discussion activities, training and education about self-esteem, and the formation of support groups that aim to increase self-confidence and develop self-potential in adolescents. The results of this service show an increase in awareness of the importance of self-esteem in adolescents in Arjasari Village. This is reflected in the increased participation of adolescents in group discussion activities, the higher the level of self-confidence of adolescents, and the more active participation of adolescents in social and community activities.